Low-Flow Anesthesia Management in Pediatric Laparoscopic Choledochal Cyst Excision and Hepaticojejunostomy: A Case Report - Togi Stanislaus Patrick; Aribawa, I Gusti Ngurah Mahaalit; Ra Ratumasa, Marilaeta Cindryani; Anak Agung Gde Adistaya (Jurnal Anestesiologi dan Terapi Intensif, 2025)
Laparoscopic surgery offers significant benefits in pediatric populations but presents anesthetic challenges, especially during prolonged procedures. This case report describes the anesthetic management of an 11-year-old boy who underwent nearly 12 hours of laparoscopic choledochal cyst excision, Roux-en-Y hepaticojejunostomy, and cholecystectomy. Low-flow anesthesia using sevoflurane was administered via a Dräger Perseus A500, enabling precise control of anesthetic delivery, oxygenation, and ventilation. Throughout the procedure, inspired oxygen fraction (FiO₂) was maintained above 30%, and end-tidal CO₂ (EtCO₂) remained stable around 35 mmHg. Volatile agent consumption was reduced, with age-adjusted MAC (xMAC) consistently between 0.85 and 0.90. Intraoperative hemodynamics and postoperative recovery were stable, with no immediate complications. This case highlights the safety, efficiency, and cost-effectiveness of low-flow anesthesia in complex pediatric laparoscopic surgery when guided by advanced monitoring systems and supports its broader adoption in resource-limited healthcare settings.